Familial assimilation in transmission of raw-freshwater fish-eating practice leading to clonorchiasis - Qian, Men-Bao (PLoS Negl Trop Dis, 2020)
Clonorchiasis is caused by raw-freshwater fish-eating practice and causes high burden in Asia. Transmission mechanism of this behavior hasn’t been illuminated, which hinders the adoption of sustainable control activities. A cross-sectional survey was implemented in students from four endemic provinces in China. Data with 23,222 students aged 9–18 and their parents were eligible. Familial clustering of raw-eating practice, impact of parents’ practice on children, interaction of spouses’ practice was analyzed. Raw-eating practice met β-binomial distribution (χ(2) = 0.8, p>0.05). Clustering coefficient increased by students’ age (R(2) = 0.82, p<0.001) and was higher in those families with boys compared to girls (t = 4.1, p<0.01). The proportion of students with raw-eating practice increased yearly by 8.9% in girls and 10.5% in boys. Compared to those without parents’ raw-eating practice, adjusted odds ratio of students’ raw-eating practice was 10.5 (95% confidential intervals (95% CI): 9.4–11.7) in those with fathers’ practice, 33.6 (95% CI: 26.3–42.9) in those with mothers’ practice and 47.1 (95% CI: 42.0–52.8) in those with both parents’ practice. There existed interaction between spouses’ practice (χ(2) = 6713.1, p<0.001) and the impact from husband on his wife was higher than that from wife on her husband. Familial assimilation characterizes the transmission of raw-freshwater fish-eating practice, consisted of vertical intergenerational assimilation from parents to their children and horizontal martial assimilation between spouses. A sustainable strategy against clonorchiasis should interrupt the transmission of raw-freshwater fish-eating practice. Additionally, further studies are expected to explore more information, e.g. the frequency in raw-eating practice and type of raw freshwater fish, infection status of C. sinensis in participants, as well as direct collection of parents’ eating information from themselves.